Influenza vaccination rate and its association with chronic diseases in China: Results of a national cross-sectional study. Issue 11 (4th March 2020) - Fan, Jing; Cong, Shu; Wang, Ning; Bao, Heling; Wang, Baohua; Feng, Yajing; Lv, Xueli; Zhang, Yang; Zha, Zhenqiu; Yu, Lianzheng; Yang, Ting; Wang, Linhong; et al.
Highlights: The influenza vaccination rate was 2.4% from a national cross-sectional study. The rate was 3.8% for people ≥60 years and 4.0% for chronically ill people. The rate was 3.6% for COPD patients and 4.8% for chronic bronchitis patients. Widespread reimbursement vaccination policy for the old is needed. Strategies towards patients with chronic diseases need urgent attention. Abstract: Introduction: Influenza vaccination is the most effective way to prevent influenza. Few studies on its rate were reported throughout China and for populations with chronic diseases. An estimation of the rates in China was accomplished. Methods: All data were from a national cross-sectional survey of a sample representing the population aged 40 years or older in mainland China in 2014–15. A total of 74, 484 individuals with complete self-reported influenza vaccination status were analyzed in 2018–19. Results: The overall influenza vaccination rate was 2.4% (95% CI 1.4–3.3) with 1.7% (95% CI 1.2–2.2) for the age group 40–59 years and 3.8% (95% CI 1.6–5.9) for the group ≥60 years. The rate was 4.0% (95% CI 2.0–5.9) among people with a chronic disease. People with asthma and people with emphysema had the highest rates (7.1%, 95% CI 3.2–11.0 and 6.6%, 95% CI 3.6–9.7) while people with chronic obstructive pulmonary disease (COPD) and people with chronic bronchitis had the lower rates (3.6%, 95% CI 2.0–5.2 and 4.8%, 95% CI 2.6–7.0). The rate was the highest among former smokers (3.3%, 95% CI 2.3–4.4) compared to current smokers (1.8%, 95% CI 0.9–2.7) and never smokers (2.5%, 95% CI 1.4–3.6). People living with finance-reimbursed vaccination policy, a positive factor for vaccination, had a higher vaccination rate (11.5%, 95% CI 10.8–12.2) (p < 0.05). People with older age, higher education level, occupation of professionals or technical personnel, living in rural areas or Northern China, former/never smoking were more likely to be vaccinated (p < 0.05). Conclusions: The influenza vaccination rate is low among adults aged ≥40 years, those ≥60 years and those with chronic diseases in China. Reimbursement policy targeting the elderly should be implemented widely and strategies towards patients with chronic diseases need urgent attention to increase the influenza vaccination coverage.